Organizational structure for electronic commerce - Ho, Wei Loong (2008)
While a growing number of companies have taken the plunge into the growing e-commerce industry, many have developed the organizational structure for e-commerce based on conventional business models. Even though conventional business models have served traditional brick and mortar firms well, it may not be the best model to be an effective e-commerce player.